Factors affecting sustainable consumption practices among female adolescents in Peninsular Malaysia - Othman, Mumtazah; Yahaya, Nurizan; Salleh, Naimah; Zainal Badari, Shamsul Azahari; Osman, Syuhaily (2008)

(untitled)
Sustainable consumption is the use of goods and services that satisfy basic needs and improve quality of while minimizing the use of irreplaceable natural resources and the byproducts of toxic materials, waste, and pollution. It is the umbrella term used for issues related to human needs, equity, quality of life, resource efficiency, waste minimisation, life cycle thinking, consumer health and safety, and consumer sovereignty. Thus, the awareness on the sustainable consumption practices is vital and should be nourished in each consumer especially among the younger generations. The objective of this study was to examine factors that contribute to sustainable consumption practices among female adolescents. A total of 334 secondary school students were randomly selected from schools in Peninsular Malaysia. The schools were randomly selected to represent northern, southern, eastern and western zones of Peninsular Malaysia. The data were collected in August 2007 using self-administered questionnaire. Eleven statements were used to measure the level of sustainable practices using 4 point Likert scale (“All the Time”, “Always”, “Seldom”, and “Never). Sample consisted of female students with an average age of 16 years. Majority of them have both parents with educational background only at high school level. Average family income was RM 2010 (USD 570). Regression analysis showed four predictor variables accounted for 22.8 % of variance in the sustainable consumption practices score (F=4.54,df 4, p=0.001). Mother educational level (β=-3.319, p=0.001),and attitude towards sustainable consumption (β=2.292, p=0. 023) were significantly related to sustainable consumption practices but not father educational level and level of knowledge on sustainable consumption. In conclusion, mother educationl level makes a better predictor for the sustainable consumption practices among female adolescents. The study implied that education is crucial for women to be more prepared in order to promote sustainable consumption practices in families.